New trends in postgraduate teaching-medicine specialization - Olascoaga-Mesía, Ana Cecilia (2019)
Medical residency is a period of intense learning in service. New trends in medical education also involve medical residents and we are currently witnessing its evolution. These new trends involve changes in the organization of programmes and in the design of competency-based specialization programs, innovation in teaching strategies and evaluation strategies, the care of the learning climate and the accreditation of programs. A summary of these trends is presented and some national and international experiences are described.